Acute and adaptation effect of high-intensity interval training on testosterone, cortisol and performance among collegiate running athletes - Eddy Purnomo; Novita Intan Arovah; Sumaryanto Sumaryanto (Termedia Publishing House, 2023)
Purpose Testosterone and cortisol need to be monitored during training and recovery periods to optimise performance and avoid overtraining. This study aimed to assess the acute and adaptation effects of high-intensity interval training (HIIT) on testosterone and cortisol levels and athletic performance among collegiate athletes. Methods This research was a one-group pretest and post-test design in 20 collegiate running athletes (20.2 ± 0.7 years old) participating in a 6-week, one-hour thrice-weekly HIIT program. Outcome variables included 100-metre running performance, maximum oxygen capacity (VO 2 max), testosterone, and cortisol serum. Rating of perceived exertion (RPE), heart rate, and blood pressure were monitored to assess the exercise intensity. Assessments were conducted before the program (T0), immediately after the first session (T1), and at the end of the 6-week HITT program (T2). The outcomes were assessed using the Friedman test. The post hoc pairwise comparisons were evaluated using the Wilcoxon igned-rank test. Results Rating of perceived exertion, heart rate, and blood pressure increased in T1 and T2, indicating that the athletes achieved high exercise intensity. Testosterone increased from T0 to T1 ( p = 0.009) but levelled off in T2 ( p = 0.668). No change in cortisol or the testosterone/cortisol ratio was demonstrated over time. Improvements in RPE ( p < 0.001), VO 2 max ( p = 0.002), and 100 m running performance ( p = 0.00) were demonstrated from T1 to T2. Conclusions The program improves athletic performance, although it has limited effects on testosterone and cortisol levels. Further research using randomised control trials, larger sample sizes and extended follow-up periods is recommended to confirm these findings.